Family-based care through foster care in Malaysia: a post-2016 child act amendment analysis / Nadhilah A.Kadir - A.Kadir, Nadhilah (2023)
Despite the recognition of family-based care after the amendments to the Child Act 2001 in 2016, a significant number of children in Malaysia continue to reside in institutional care facilities. Extensive research indicates that institutional care can have detrimental effects on a child's holistic development, encompassing physical, intellectual, and mental aspects. In light of these concerns, the prioritization of family-based care is imperative to ensure the well-being of children and to safeguard their inherent right to grow within a family environment. Foster care stands out as a prominent alternative within the realm of family-based care. Presently, Malaysia lacks specific legislation dedicated solely to foster care, with the Child Act 2001 containing limited provisions, some of which have been amended after 2016. Furthermore, the Child Act 2001 does not expressly permit agencies beyond the Social Welfare Department to formally assess the suitability of foster parents. Consequently, institutional care remains a prevalent placement choice for children in need of care and protection, while opportunities for foster care placements remain scarce. This research embarks on a comprehensive analysis of the amendments to the Child Act 2001 concerning foster care as an alternative care solution for children in need of care and protection. The study also delves into the international legal framework for foster care. Employing a qualitative research methodology comprising library research and content analysis, this study endeavors to inform policy and legislative improvements. The findings of this research suggest that legal and policy reforms are necessary to strengthen foster care as a viable alternative for children in need of care and protection. The study focuses primarily on the Child Act 2001 and the international legal framework for foster care. The implications of this research extend to child welfare policies, legal frameworks, international alignment, government commitments, and the promotion of family-based care. It also underscores the importance of comprehensive research in addressing the complex issues related to child protection. The expected outcomes of this research align with the Malaysian government's commitment to building an inclusive society that prioritizes children's well-being and fortifies the child protection system. This initiative resonates with the National Child Policy, the National Child Protection Policy, the Twelfth Malaysian Plan (RMK12), and the United Nations Sustainable Development Goals (SDGs) to ensure the holistic welfare and protection of Malaysia's children.